Analysis of Professional Competency Development on the Performance of Guidance and Counseling Teachers Madrasah Aliyah - Rismanila; Bahrun; Niswanto (Pascasarjana Universitas KH. Abdul Chalim, 2025)
This research aims to analyze and develop a professional competency development strategy for Guidance and Counseling Teachers' (BK) performance at Madrasah Aliyah Negeri (MAN) Aceh Besar. This study uses a quantitative approach involving the Principal and BK Teachers as research subjects. Data was collected through in-depth interviews, observations, documentation, and questionnaires. The study results show that professional competence influences the performance of BK teachers. The development of the professional competence of BK teachers at MAN Aceh Besar still needs improvement, especially in the use of educational technology and innovative approaches to student guidance. Some identified strategies include continuous training, increased teacher collaboration, and school managerial support. This study concludes that structured and sustainable professional competency development is very important to improve the quality of school guidance and counselling services. The implications of this study are expected to be the basis for developing more effective training programs and policies for BK teachers in MAN Aceh Besar and similar educational institutions.